Flexible and Transparent Ionic Liquids/Poly(vinylidene fluoride) Composition‐Gradient Piezo‐Active Composites for Highly Sensitive Pressure Sensor - Hao Bao; Yizhou Ma; Jiatai Sun; Qiuying Zhao; Lu Yang; Ying Hou; Haiyan He; Huajie Huang; Hongli Ji; Jinhao Qiu (Advanced Electronic Materials, 2023)
Abstract Nowadays, the advent of pressure sensors for intelligence terminal devices and skin‐inspired electronics has trigged rapid development of flexible, sensitive, and transparent sensing materials. Piezo‐active poly(vinylidene fluoride) (PVDF) is emerging as a promising candidate for sensing components due to the flexible and transparent features. However, the inherent weak piezo‐activity and consequently low sensitivity of PVDF remains a challenge for its sensing applications. Herein, ionic liquids ([EMIM]Cl) additive combined with a composition‐gradient multilayered architecture design are employed to hardness the piezo‐response of PVDF. The resultant composites present ultra‐high piezoelectric coefficient d33 of 39 pC N−1, which is 2.78 times that of PVDF. Meanwhile, the transparent ILs dopant enables the composites with superior transparency (87%). With notable advantages of high transparency and piezoelectricity, the ILs/PVDF composites exhibit high sensitivity of 0.0423 V N−1, ultra‐fast recovery time of 0.2 ms and stable operation capability when coupled with metal electrodes, confirming their applicability for reliable pressure sensor.